Evaluasi Kesesuaian Peresepan Obat Pasien Kronis BPJS Rawat Jalan Poliklinik Penyakit Dalam Terhadap Formularium Nasional dan Formularium Rumah Sakit Di Rumah Sakit Umum Harapan Bunda Jakarta Timur Periode Oktober-Desember Tahun 2024: Evaluation of Prescription Compliance for Chronic Patients at the Internal Medicine Outpatient Clinic of BPJS with the National Formulary and the Hospital Formulary at General Hospital X, East Jakarta, October–December 2024 - Mazdalifah Komalasari; Imam Syafi”i; Julia Totong (UIMA Press, 2025)
BPJS Kesehatan continues to face financial challenges, partly influenced by noncompliance with the National Formulary (Fornas) in drug prescribing, which may lead to healthcare budget inefficiency. This study aimed to evaluate the conformity of chronic drug prescriptions among outpatient BPJS patients based on adherence to the National Formulary and Hospital Formulary and to identify diseases and medications not listed in the National Formulary at the Internal Medicine Clinic of Harapan Bunda General Hospital, East Jakarta, during October–December 2024. This study employed a non-experimental descriptive design with a retrospective approach using 100 chronic prescription sheets obtained through total sampling. Data were collected through prescription document review and analyzed descriptively using univariate analysis. The results showed that prescription conformity with the National Formulary was 87.14%, while conformity with the Hospital Formulary reached 100%. Hypertension was identified as the disease with the highest number of noncompliant prescriptions. The most frequently prescribed non-formulary drugs were disflatyl, braxidin, and urogetic, which are not considered first-line therapies for chronic diseases. This study concludes that noncompliance with the National Formulary in chronic drug prescribing among outpatient BPJS patients remains present and is influenced by patient clinical factors as well as physicians’ prescribing habits and individual considerations.